The influence of using Stripe, Firebase, and OpenAI in sophisticated API solutions - Shalom Izakr Drofa (Multidisciplinary Journal of Akseprin Indonesia, 2024)
This research examines the effect of incorporating Stripe, Firebase, and OpenAI into advanced API solutions to enhance user experience (UX) in web and mobile applications. This study employs a case study examination of existing apps utilizing these APIs, incorporating empirical data collection, performance metrics evaluation, and user feedback assessment to determine the effectiveness of the APIs. Experiments are conducted to evaluate API integration, comparing the application's performance before and after the integration. Key performance indicators, including transaction success rate, data synchronization velocity, and AI-driven engagement metrics, were employed to assess the influence on user experience. Data was collected from application logs, user interaction reports, and developer insights to finalize the evaluation. The report characterizes UX optimization as encompassing loading speed, navigational ease, transaction velocity, real-time response, and engagement metrics. Our findings indicate that Stripe decreases the checkout abandonment rate by 40% and enhances the transaction success rate by 30%, consequently augmenting user trust in transactions and improving financial transaction efficiency. This reduces data synchronization latency by around 70%, resulting in a more seamless application experience and improved retention rates. The AI models from OpenAI increase session durations by 25-40% and promote engagement through improved user interaction via a more tailored experience. Scientific evidence substantiates the specific benefits of API integration, such as decreased latency, enhanced interactivity, and accelerated application processes. The research identifies them as integration problems and outlines effective practices for future API implementations. This study effectively proposes methods for enhancing user experience through the implementation of APIs